PENGARUH TINGKAT SALINITAS TERHADAP MORFOLOGI EMPAT VARIETAS KEDELAI (Glycine max L.) - Triati, Desfal (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
This study aims to evaluate the effect of various salinity levels on the growth and yield of four soybean varieties. The design used was a Completely Randomized Design (CRD) with a factorial pattern of two factors and two replications. The combination of treatments consisted of 32 experimental units, each consisting of 10 plants, so that the total number of plants observed was 320 plants. The first factor was the soybean variety consisting of four levels: V1 = Burangrang, V2 = Anjasmoro, V3 = Grobogan, and V4 = Detam 1. The second factor was the salinity level of the NaCl solution with four levels: S1 = 0 mg L?¹ (control), S2 = 1500 mg L?¹, S3 = 3000 mg L?¹, and S4 = 4500 mg L?¹. The parameters observed included plant height, shoot dry weight, number of branches per plant, number of pods per plant, number of filled pods, weight of 100 seeds, and tolerance index to salinity stress. The results showed that salinity stress had a significant effect on plant height and the number of filled pods. The treatment without salinity produced the highest total number of pods, number of filled pods, and weight of 100 seeds compared to other salinity treatments.